Antioxidant potential of five commercially less valued leafy vegetables from Bangladesh (Bangladesh Journal of Botany, 2018)
To evaluate the antioxidant potential of less valued green leafy vegetables of Bangladesh, the methanolic extracts of Alternanthera sessilis, A. philoxeroides, A. paronychioides, Glinus oppositifolius and Portulaca oleracea were subjected to assay for total phenolic content, total flavonoid content and DPPH free radicle scavenging activity. Among the studied materials, A. sessilis showed the highest phenolic and flavonoid content. However, G. oppositifolius presented the lowest phenolic content (14.53 ± 0.48 mg of GAE/g of sample) and P. oleracea exhibited minimum (7.005 ± 0.25 mg of RUE/g of sample) flavonoid content. DPPH radical scavenging activity was found to increase with increase in the concentration of each individual material. A. philoxiroides (IC50 = 6.07 ± 0.27 μg/ml) was found as the most active in DPPH radical percentage inhibition, which was followed by A. sessilis (IC50 = 7.17 ± 0.67 μg/ml). Interestingly, A. paronychioides, in spite of having good amount of total phenolic and flavonoid content, showed less DPPH scavenging activity. No linear relationship was found to exist in case of the total phenolic, flavonoid content and DPPH scavenging activity among G. oppositifolius, P. oleracea and A. paronychioides. The results from different methods may differ substantially because each complex chemical reaction generates unique values. However, all the five plants exhibited creditable antioxidant activity and thus consumption of these vegetables may play important role in combating oxidative stresses and thereby help in retaining good health.